A META ANALYSIS STUDY ON THE EFFECTIVENESS OF HIGHER ORDER THINKING SKILLS (HOTS) BASED LEARNING IN SCIENCE AND MATHEMATICS SUBJECTS - binti Mohamad Hasim, Salbiah; binti Mohamad Yasin, Ruhizan; binti Rosli, Roslinda (Proceeding 7th International Seminar on Regional Education, 2015)
Abstrak Thinking ability is one of the essential components need to be mastered by the students to help them solve problems and face the challenges in various fields of education today. This meta-analysis study will examine the effectiveness of learning based on Higher Order Thinking Skills (HOTS) in Science and Mathematics. HOTS-based learning environment involves establishing ways of thinking and the acquisition of studentsâ knowledge through independent learning, active learning and student-centered learning. Online data bases, such as EBSCOhost, ProQuest, SpringerLink, Eric and Google Scholar were used to find relevant studies on HOTS-based learning in Science and Mathematics from 2005 to 2015. A total of 15 samples were selected and the data gathered was analyzed using effect sizes and coding. Six elements of HOTS used to observe the effect of HOTS-based learning are the critical thinking, creative thinking, scientific thinking, problem solving, metacognitive skills and mathematical thinking. Results from the meta-analysis revealed that HOTS greatly influence studentsâ academic achievement and the ability to solve problems. This is because the effect size obtained from the 15 selected studies show the majority of studies reveal a medium effect size. Eight studies showed medium effect size and seven studies showed large effect size. This study also identifies fourteen different types of instruments to track the effectiveness of HOTS elements. The results of this study can also be used for further research focusing on other micro elements of HOTS to identify the effectiveness and impact on any chosen subject.Keywords : The Effects of HOTS- Based Learning, meta analysis, Science and mathematics subjects.